2012
DOI: 10.1021/es300265a
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Noncovalent Interactions between Glyphosate and Dissolved Humic Substances by NMR Spectroscopy

Abstract: Interactions of glyphosate (N-phosphonomethylglycine) herbicide (GLY) with soluble fulvic acids (FAs) and humic acids (HAs) at pH 5.2 and 7 were studied by (1)H and (31)P NMR spectroscopy. Increasing concentrations of soluble humic matter determined broadening and chemical shift drifts of proton and phosphorus GLY signals, thereby indicating the occurrence of weak interactions between GLY and humic superstructures. Binding was larger for FAs and pH 5.2 than for HAs and pH 7, thus suggesting formation of hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 35 publications
(104 reference statements)
3
59
0
Order By: Relevance
“…Many studies have reported that glyphosate can be sorbed to humic acids (Piccolo et al, 1996;Banta et al, 2009;Mazzei and Piccolo, 2012). In the present study the humic acid RB4 neutralized the antimicrobial effect of glyphosate in vitro.…”
Section: Neutralisation Of Glyphosate In Vitrosupporting
confidence: 61%
See 1 more Smart Citation
“…Many studies have reported that glyphosate can be sorbed to humic acids (Piccolo et al, 1996;Banta et al, 2009;Mazzei and Piccolo, 2012). In the present study the humic acid RB4 neutralized the antimicrobial effect of glyphosate in vitro.…”
Section: Neutralisation Of Glyphosate In Vitrosupporting
confidence: 61%
“…Humic acids are classified among the polyvalent weak organic acids and possess the ability to form com-plexes. Humic substances could adsorb glyphosate in vitro (Piccolo et al, 1996;Banta et al, 2009;Mazzei and Piccolo, 2012). Also Chlorella (microalgae) and yeast showed detoxifying properties (Shim et al, 2008;Baptista et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…and Piccolo found that glyphosate may spontaneously and significantly bind to soluble humic matter by non-covalent interactions at slightly acidic pH [39]. Binding to matrices such as soluble fulvic and humic acids could be the reason.…”
Section: Discussionmentioning
confidence: 99%
“…In environmental research, NMR is becoming an important tool used to highlight specific interactions between different constituents in soils [21,[29][30][31][32]. Over the years, numerous detailed NMR studies have provided valuable information on the underlying factors regarding the different binding properties of a number of anthropogenic contaminants [31][32][33][34][35]. Recently, a novel NMR technology was introduced, termed as comprehensive multiphase (CMP) NMR [38].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel NMR technology was introduced, termed as comprehensive multiphase (CMP) NMR [38]. This approach combines hardware from solution, gel, and solid-state NMR into a single probe and permits environmental samples to be investigated in situ, in their fully hydrated state, and in all phases, allowing for all phases to be simultaneously investigated [28,[35][36][37][38]. A number of NMR techniques can be used to investigate interactions between organic soil constituents [31,36,39].…”
Section: Introductionmentioning
confidence: 99%